Sociodemographic, lifestyle and medical influences on serum testosterone and sex hormone–binding globulin in men from UK Biobank. (10th October 2020) - Yeap, Bu B.; Marriott, Ross J.; Antonio, Leen; Bhasin, Shalender; Dobs, Adrian S.; Dwivedi, Girish; Flicker, Leon; Matsumoto, Alvin M.; Ohlsson, Claes; Orwoll, Eric S.; Raj, Suchitra; Reid, Christopher M.; et al.
Abstract: Objective: Serum testosterone concentrations are affected by factors unrelated to hypothalamo‐pituitary‐testicular axis pathology. We evaluated the impact of sociodemographic, lifestyle and medical factors, on serum testosterone and sex hormone–binding globulin (SHBG) in men aged 40‐69 years. Design: Cross‐sectional analysis of 208, 677 community‐dwelling men from the UK Biobank. Measurements: We analysed associations of different factors with serum testosterone and SHBG (immunoassays) and calculated free testosterone (cFT), using smoothed centile plots, linear mixed models and effect size estimates. Results: Median (interquartile range) for serum testosterone was 11.6 (9.4‐14.1) nmol/L, SHBG 36.9 (27.9‐48.1) nmol/L and cFT 213 (178‐255) pmol/L. Age and BMI were inversely associated with testosterone and cFT, while SHBG was associated with age and inversely with BMI (all P < .001). Living with a partner, (South) Asian ethnicity, never or previous smoker and some medical conditions were associated with lower testosterone. Poultry or fish eater, and higher physical activity were associated with higher testosterone (all P < .001). Testosterone was lowered by 0.5 nmol/L across ages, 1.5 nmol/L for BMI 30 vs 25 kg/m 2, 2 nmol/L for (South) Asian ethnicity, living with partner, college/university qualifications, low red meat eater, insufficient physical activity and 0.3‐1.0 nmol/L with cardiovascular disease or diabetes. Different combinations of these factors varied serum testosterone by 4 nmol/L, SHBG by 30 nmol/L and cFT by 60 pmol/L. Conclusions: The identified modifiable risk factors support lifestyle‐based interventions in men with low testosterone concentrations. Considering sociodemographic, lifestyle and medical factors facilitates more personalized interpretation of testosterone testing results with respect to existing reference ranges.